HLA Class II influences humoral autoimmunity in patients with type 2 autoimmune hepatitis - Djilali-Saiah, Idriss; Fakhfakh, Amin; Louafi, Hamida; Caillat-Zucman, Sophie; Debray, Dominique; Alvarez, Fernando (Journal of hepatology, 2006)
Type 2 autoimmune hepatitis (AIH) is characterized by the presence of anti-liver kidney microsome (anti-LKM-1) and/or anti-liver cytosol type 1 (anti-LC1) autoantibodies. However, the correlation between these autoantibodies and the genetic background has not been studied. Frequencies of HLA class II alleles were compared between the 60 Caucasian children with type 2 AIH and 313 control subjects. The anti-LKM1 antibody reactivity directed against antigenic sites of CYP2D6 was analysed by ELISA. HLA-DQB1∗0201 allele was found to be the primary genetic determinant of susceptibility to type 2 AIH by conferring the highest odd-ratio (OR = 6.4). HLA-DRB1∗03 allele was significantly increased ( P < 0.0001) among patients with both anti-LKM1 and anti-LC1 autoantibodies as well as in those with only anti-LC1 + compared to those with anti-LKM1 + alone. In contrast, HLA-DRB1∗07 allele was significantly associated ( P < 0.0001) with anti-LKM1 + alone compared to groups with both anti-LKM and anti-LC1 or with LC1+ alone. Children with the DRB1∗07 allele develop anti-LKM1 autoantibodies having a more restricted specificity (2 epitopes) than to those having HLA-DRB1∗03 allele (5 epitopes). The HLA-DR locus is involved in autoantibody expression, while the DQ locus appears to be a critical determinant for the development of type 2 AIH.